Metabolic Profiling and Post-harvest Behavior of “Dottato” Fig (Ficus carica L.) Fruit Covered With an Edible Coating From O. ficus-indica - Allegra, Alessio; Gallotta, Alessandra; Carimi, Francesco; Mercati, Francesco; Inglese, Paolo; Martinelli, Federico (Frontiers in Plant Science, 2018)
Fig fruit are usually highly sensitive to some physiopathological disorders during post-harvest life, such as softening and skin cracking. Indeed, the use of edible coating (EC) has been evaluated in several fruit crops to reduce fruit post-harvest transpiration and to maintain fruit visual quality. The aim of this study was to determine the post-harvest metabolic response of breba figs treated with mucilage extract from O. ficus-indica cladodes, using an untargeted metabolomic approach. Coated and non coated (control) fruit were sealed in plastic bags, and stored at 4 °C for 7 days. The effect of the edible coatings on their shelf-life and qualitative attributes were evaluated by analyzing the fruit primary metabolism and other qualitative parameters such as total soluble solids content, titratable acidity, fresh weight loss and firmness. Results underlined that edible coating was effective in maintaining fruit fresh weight, and fruit firmness. Stepwise discriminant analysis was able to discriminate fruit conditions. Alanine, xylulose, aspartic acid, glutamic acid and 2,5-dihydroxypyrazine showed a significant role on discriminating edible coated fruit from untreated ones. Principal component analysis was able to highlight clear differences in the overall metabolism changes between untreated and treated fruit. The application of EC significantly mitigated the decrease of most of the aminoacid content during shelf-life. EC treatment caused the changes of several organic acids in comparison to untreated control, increasing the amount of carbohydrates and other key metabolites, such as beta-sitosterol, glycerol and uracil. These results clearly showed the drastic effects of EC on fig metabolism during post-harvest and shed light on the beneficial mechanisms of this treatment.